Perspectives on in situ Sensors for Ocean Acidification Research - Sastri, Akash R.; Christian, James R.; Achterberg, Eric P.; Atamanchuk, Dariia; Buck, Justin J. H.; Bresnahan, Philip; Duke, Patrick J.; Evans, Wiley; Gonski, Stephen F.; Johnson, Bruce; Juniper, S. Kim; Mihaly, Steve; et al. (Frontiers in Marine Science, 2019)
As ocean acidification (OA) sensor technology develops and improves, in situ deployment of such sensors is becoming more widespread. However, the scientific value of these data depends on the development and application of best practices for calibration, validation, and quality assurance as well as on further development and optimization of the measurement technologies themselves. Here, we summarize the results of a two-day workshop on OA sensor best practices held in February 2018, in Victoria, British Columbia, Canada, drawing on the collective experience and perspectives of the participants. The workshop on In Situ Sensors for Ocean Acidification Research was organized around three basic questions: 1) What are the factors limiting the precision, accuracy and reliability of sensor data? 2) What can we do to facilitate the quality assurance/quality control (QA/QC) process and optimize the utility of these data? and 3) What sort of data or metadata are needed for these data to be most useful to future users? A synthesis of the discussion of these questions among workshop participants and conclusions drawn is presented in this paper.